METHODS OF EXPERIMENT IN PHYSICS IN VOCATIONAL SCHOOLS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
This article has taken an important place in the curriculum "Software Development", based on the fact that physics is primarily a fundamental science. Its main task is to contribute to the development of the content of the methodology of teaching physics.